THE ROLE OF TUMOR NECROSIS FACTOR SUPERFAMILY MEMBER 14 (TNFSF14/LIGHT) IN PERIODONTAL DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS - Dr. Tejinder Pal Singh; Dr. Taruna Mahant; Dr. Rajat Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Periodontitis is a multifactorial, chronic inflammatory disease initiated by dysbiotic microbial biofilms that leads to the progressive destruction of the periodontium, the specialized tissues that surround and support the teeth¹⁻³. If left untreated, this destruction can result in tooth loss, significantly impacting oral health, quality of life, and systemic health⁴. The global prevalence of severe periodontitis is estimated to be around 10-15% of the adult population, making it a major public health concern⁵.